Materialistic desires and the ethical life in the Analects and the Mencius - TAN, Sor-hoon (Institutional Knowledge at Singapore Management University, 2014)
A consideration of Confucian ethics that employs the work and concerns of the eminent comparative ethicist Joel J. Kupperman.